2012
DOI: 10.1111/j.1348-0421.2012.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Potent effects of, and mechanisms for, modification of crosstalk between macrophages and adipocytes by lactobacilli

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…In the latter situation, strains such as CRL117, CRL350, CRL143 CRL575, CRL1446, and CRL66 could be useful. Miyazawa et al demonstrated that increased pro-inflammatory cytokines (IL-6, IL-12, and TNF-α) inhibited the differentiation of a fibroblast cell line (3T3L1) in adipocytes, suggesting that acute inflammation stimulated by lactobacilli could be the mechanism by which adipogenic differentiation is suppressed, leading to adipocyte hypertrophy (33). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter situation, strains such as CRL117, CRL350, CRL143 CRL575, CRL1446, and CRL66 could be useful. Miyazawa et al demonstrated that increased pro-inflammatory cytokines (IL-6, IL-12, and TNF-α) inhibited the differentiation of a fibroblast cell line (3T3L1) in adipocytes, suggesting that acute inflammation stimulated by lactobacilli could be the mechanism by which adipogenic differentiation is suppressed, leading to adipocyte hypertrophy (33). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that microbial products associated with immunobiotics (immunoregulatory probiotics) can also cross the intestinal barrier, being able to modulate distant tissues (such as adipose tissue) through the induction of changes in cytokine profiles (32). Miyazawa et al in an in vitro study using conditioned medium showed that different lactobacilli may suppress differentiation of preadipocytes through macrophage activation and alter the immune responses of macrophages to adipose cells (33). …”
Section: Introductionmentioning
confidence: 99%
“…rhmanosus LA-2 mediated up-regulation was unknown. In addition, we previously used the conditioned medium of murine macrophage-like cell line J774.1 cultured with LGG or TMC0356 strains to stimulate mouse preadipocyte cell line 3T3-L1 and found a suppressed lipid accumulation and reduced PPAR-γ mRNA expression [ 19 ]. Moreover, the J774 cells treated with Lactobacillus GG or L .…”
Section: Discussionmentioning
confidence: 99%
“…gasseri TMC0356 improved the production of IL-6 and IL-12 [ 19 ]. The conditioned medium from lactobacilli-cultured J774.1 cells transferred to the preadipocyte cell line 3T3-L1 significantly suppressed lipid accumulation and decreased peroxisome proliferator activated receptor γ (PPAR-γ) [ 19 ]. Similarly, Park et al [ 20 ] showed that exposure of 3T3-L1 adipocytes to L .…”
Section: Introductionmentioning
confidence: 99%
“…Because pulmonary TNF‐α gene expression was upregulated by LGG administration in the present study, the resultant proinflammatory status may have led to further increases in body weight and fat. On the other hand, our previous study showed that LGG administration reduces lipid accumulation in the murine pre‐adipocyte cell line 3T3‐L1 thorough TNF‐α production by the murine macrophage‐like cell line J774.1 . Unfortunately, we did not examine markers associated with obesity in adipose tissue in the present study.…”
Section: Bacterial Profiles Of Each Group According To T‐rflp Analysismentioning
confidence: 75%